An Analysis of the Effects of Public Debt on Exchange Rate Volatility in Uganda for a Period of 53 Years 1970–2023 - Bosco Bidali (Uganda Christian University, 2024)
Uganda, like other developing countries, has been experiencing a rising trend in public debt, raising concerns among the public about its implications on economic variables influencing economic welfare. Notably, Uganda's exchange rate has exhibited a depreciating and volatile trend since 1970 to date, detrimental to economic growth. This study empirically investigates the effects of public debt on exchange rate volatility in Uganda from the period 1970 to 2023. This study examines the short run and long run relationship between external debt, debt servicing non external debt, foreign reserves, and exchange rates using an ARDL-ECM model. The findings disclose that external debt has an insignificant positive effect in the short run and an insignificant negative effect in the long run. In contrast, external debt service has an insignificant positive effect in the long run, meanwhile foreign reserves have a significant negative effect in the long run and a positive relationship in the short run. Based on these findings, the government should prioritize maintaining stable foreign reserves to mitigate exchange rate volatility in the short and long run. Additionally, prudent debt management and investing public debt in high-multiplier projects can enhance Uganda's capacity to repay debts and interest charges. Furthermore, concessional loans are more suitable for developing economies like Uganda.